Robinson Crusoe - Defoe, Daniel, 1661?-1731 (Oxford University Press, 1998)
Crusoe leaves the English coast for Africa and finds himself the sole survivor of a shipwreck. On a desert island, he finds another human footprint on the shore, encounters cannibals, and befriends a native.
Originally issued in series: World's classics.
Keywords: Crusoe, Robinson -- (Fictitious character); Crusoe, Robinson (Fictitious character) -- Fiction.; Shipwreck survival -- Fiction.; Castaways -- Fiction.; Solitude -- Fiction.; Islands -- Fiction.; Survie après naufrages -- Romans, nouvelles, etc.; Naufragés -- Romans, nouvelles, etc.; Solitude -- Romans, nouvelles, etc.; Îles -- Romans, nouvelles, etc.; FICTION -- Action & Adventure.; Castaways; Islands; Shipwreck survival; Solitude; Fiction; Adventure fiction.; Action and adventure fiction.